Biodegradation of chlorobenzene and chlorophenols by pseudomonas cultures - Bhaskar, Gaikwad G.; Rita, Varma J. (Research Journal of Chemistry and Environment, 2013)
Cultures from NCIM culture collection (National Chemical Laboratory, Pune, India) were screened for biodegradation chlorobenzene (CB). A strain, Pseudomonas sp. NCIM 2303, was found to be most effective. The biodegradation was carried out in aqueous solution by resting cells. The decomposition of 0.02% CB was 96.64% in 24h. We have screened cultures for biodegradation of o-chlorophenol and p-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 94.59% degradation of 0.15% o-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 31.42% degradation of 0.2% p-chlorophenol.
Keywords: Biodegradation; chloride; chlorobenzene; etc.; pollution; Pseudomonas sp

Green approach to dye wastewater treatment using biocoagulants - Chethana, M.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Raja, S.; Ranade, Vivek V. (ACS Sustainable Chemistry & Engineering, 2016)
The present study focuses on newer biocoagulants, bioformulations, and the understanding of coagulant behavior with biocoagulants in relation to chemical coagulants. Newer biocoagulants, seeds of Azadirachta indica (AI) and pads of Acanthocereus tetragonus, are discussed along with two known biocoagulants, Moringa oleifera and Cicer arietinum seeds. Dye removal studies were carried out using widely reported Congo red dye to facilitate easy comparison with other conventional coagulants and the effect of various parameters such as initial dye concentration, pH, coagulant dose, etc. are discussed in detail. The use of biocoagulant was found to be highly effective, and up to 99% dye removal was achieved for coagulant doses in the range of 300-1500 mg/L. It was also observed that coagulation is pH sensitive, similar to chemical coagulants. Although the biocoagulant dose is relatively higher than the conventional chemical coagulants, a good value for the sludge volume index, similar to 50 mL/g for 1 h and 30 min, respectively, was obtained for the two coagulants, Acanthocereus tetragonus and Moringa oleifera. A very high particle count compared to chemical coagulants was observed using a focused beam reflectance measurement. Bioformulation with chemical coagulants such as alum, ferric, and aluminum based coagulants can, not only lower doses of biocoagulants (up to one-third) but can also result in significant improvement in the coagulation performance, up to 50% or more.
Keywords: coagulation; dye removal; Effluent treatment; flocculation; pollution

Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater

Hydrodynamic cavitation using vortex diode: an efficient approach for elimination of pathogenic bacteria from water - Jain, Pooja; Bhandari, Vinay M.; Balapure, Kshama; Jena, Jyotsnarani; Ranade, Vivek V.; Killedar, Deepak J. (Journal of Environmental Management, 2019)
The present study successfully demonstrates greener methodology of hydrodynamic cavitation using rotational flows for disinfection of water. Disinfection of two model microbial strains-gram-negative (Escherichia colt) and gram-positive (Staphylococcus aureus) using vortex diode was evaluated. The removal efficacy was quantified for two different cavitation reactors. Practically complete elimination of E. coli was achieved (99%) after 1 h of cavitation at a pressure drop of only 0.5 bar. However, elimination of S. aureus using vortex diode was observed to be lower in comparison to the removal of E. coli and only 60% disinfection could be achieved under similar conditions, which can be subsequently enhanced up to 98% by increasing pressure drop. The results were compared with another cavitating device that employs linear flow for cavitation, orifice. The reactor geometry has significant impact on the disinfection process and orifice was found to require significantly higher pressure drop (10 bar) conditions for disinfection and for eliminating grain-positive bacteria with high efficiency. A plausible mechanism for disinfection was proposed to elucidate the role of cavitation in cell destruction leading to death of cells through the rupture of cell wall, oxidative damage and possible DNA denaturation. Also, a cavitation model using per pass disinfection was developed that can provide meaningful physical description of the disinfection process as against the conventional first order reaction rate model. This study would provide meaningful insight into cavitation process based on hydrodynamic cavitation for the destruction of both gram-negative and gram-positive bacteria from various water sources, including industrial wastewaters.
Keywords: Cavitation; Disinfection; kinetics; pollution; Wastewater treatment

Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Wastewater treatment and process intensification for degradation of solvents using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Chemical Engineering and Processing-Process Intensification, 2021)
Industrial wastewater treatment for removal of small concentrations of harmful solvents is pertinent issue in many chemical and pharmaceutical industries. The present work evaluates removal of three common solvents by hydrodynamic cavitation (nominal capacity, 1m(3)/h). Solvent degradation of three solvents viz. octanol, dimethyl formamide and cyclohexanol was studied in the concentration range of 50-200 mg/L and for the pressure drop range of 0.5-5 bar. The vortex based cavitation device (vortex diode) was compared with that of linear flow based device (orifice). Process intensification in the form of aeration and addition oxidizing agent-hydrogen peroxide was also evaluated for synergistic effect. The vortex diode required lower pressure drop and is superior to orifice and process intensification using aeration is most effective. A reduction in TOC to the extent of 74% could be achieved for octanol (200 ppm) using aeration with cavitational yield of 1202x10(-4) mg/J for vortex diode, yield similar to 10 times of orifice. The degradation depends on the nature of solvent and it was revealed that low values of dielectric constant (epsilon<10) favour degradation. The kinetics was evaluated using rate model based on per-pass degradation factor. The process techno-economic feasibility is useful in industrial wastewater treatment.
Keywords: Cavitation; Effluent; Organics removal; Oxidation; pollution

Degradation of API pollutants using hydrodynamic cavitation and process intensification - Divya Dixit; Pooja Thanekar; Vinay M. Bhandari (Chemical Engineering and Processing - Process Intensification, 2022)
Degradation of Naproxen, a common nonsteroidal anti-inflammatory drug as a model compound, has been reported using hydrodynamic cavitation (HC) and process intensification. Two types of cavitating devices, vortex diode that employs vortex flow and a conventional linear flow based device, orifice have been investigated for their effectiveness in degradation. Process intensification was carried out by employing simple aeration and also by addition of oxidising agent, hydrogen peroxide (H2O2). Vortex diode required significantly lower pressure drop (1.5 bar) compared to the orifice (5 bar). A high extent of degradation, 67%, was possible using the process intensification; representing a very high enhancement, to an extent of more than 200%, by combining HC+H2O2. The degradation of naproxen progresses via intermediates formation and intermediates also eventually get gradually degraded. The kinetics of degradation was evaluated using per pass degradation model and for the different approaches, confirming higher per-pass degradation in the vortex diode and for the process intensification. The cavitational yield in HC+H2O2+aeration using vortex diode (23.4 × 10−5 mg/J) was ∼ 5 times greater than that for orifice (4.5 × 10−5 mg/J). The present study clearly highlights utility of process intensification approach for the degradation of active pharmaceutical ingredients (API) pollutants for increased efficacy.
Keywords: Naproxen: Oxidation; Pharmaceutical; pollution; Wastewater treatment

Developing spherical activated carbons from polymeric resins for removal of contaminants from aqueous and organic streams - Mane, M. B.; Bhandari, V. M. (International Journal of Environmental Science and Technology, 2022)
Spherical activated carbons from polymer resin were developed with metal modifications, before/after carbonization using copper and nickel, for gradation of zeta potential (-5.01 to 8.64 mV) and high metal loading (up to 12.3%). The materials provide improved removal of various contaminants from aqueous and organic streams-removal of bacteria from water and sulfur removal from fuel. The metal-modified spherical activated carbons were highly effective for removal of both gram-negative E. coli and gram-positive S. aureus bacteria. The copper-modified spherical activated carbon could eliminate 99.9-100%, both bacterial content proving efficacy in water disinfection with a very high rate similar to 1.33 x 10(5) (CFU/ml.s). The zeta potential has significant impact with higher disinfection for high values; similar to 10-15% disinfection can be improved up to 100% for zeta potential changes from -5 to 8.6 mV. Kinetics of disinfection was studied by accounting for zeta potential in the conventional rate model, and the efficacy of both the models was compared. The fit of revised model was excellent. The spherical activated carbons can be useful for removal of slightly polar contaminants from organic streams and a high capacity of 12.8, 20 and 28 mgS/g for thiophene, benzothiophene and dibenzothiophene, respectively. The developed materials can provide useful applications in the area of environmental pollution control. [GRAPHICS] .
Keywords: Adsorption; Material; pollution; Sulfur removal; Water disinfection

Dual activity cavitation reactors for increased efficacy in degradation of refractory pollutants-A case study on cephalexin degradation - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
The present work discloses a new form of cavitation processes using reactors of dual activity for increased efficiency. A proof of concept is established for the degradation of a refractory pollutant-cephalexin using both conventional and dual function cavitation reactors for the first time using acoustic and hydrodynamic cavitation (HC). A vortex diode as a cavitating device was employed for HC using aluminium as a non-catalytic and copper as dual function device for providing additional catalytic effect. The process in-tensification using hydrogen peroxide (H2O2) coupled with the dual function devices was highly effective. A negligible degradation with only HC and 81% for HC coupled with H2O2 in 60 min for Al-vortex diode compared to 100% degradation in only 5 min for the copper device clearly demonstrates the order of magnitude enhancements establishing dual function due to catalytic activity. Also, pH modification (pH 11) yields enhancement over 300% for Cu-vortex diode. The use of dual function reactors drastically reduces H2O2 do-sage. The overall enhancements in the per pass degradation and cavitation yields were huge, similar to 3000% and 1450% respectively, highlighting the potential of the dual function ca-vitation reactors in real-life applications, not just for increased efficiencies but also for significantly reduced costs.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Advanced oxidation; Degradation; pollution; Technology; Wastewater treatment

Enhanced degradation of metformin using surface-coated vortex diodes - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical engineering and processing-process intensification, 2023)
The present work successfully demonstrates, for the first time, complete degradation of metformin using newer surface-coated vortex diode (SCVD) with copper and nickel coating to provide catalytic activity in the conventional hydrodynamic cavitation (HC) for significantly enhanced degradation efficiency. The SCVDs have dual functionality and the efficacy of catalytic cavitation reactors get enhanced using process intensifications of the type H2O2 addition, pH modification, and combined approach of HC+ pH+ H2O2 apart from the advantage of low pressure drop for the vortex flow based cavitation in vortex diode (Delta P of 1 bar). Complete, 100%, degradation of metformin (MTF) was achieved within 5 min with integration of optimized H2O2 dose and exceptionally high synergistic index value over 300, indicating extraordinary synergy for both Cu and Ni-SCVD. Acidic condition promote degradation and a complete degradation with a high 43-48% mineralization was observed using HC+ pH 4+ (1:200) H2O2 with less intermediates formation. The SCVDs reveal remarkable enhancement of similar to 9800% in per-pass degradation and 1400-3400% in cavitational yield as compared to conventional cavitation process under similar conditions. The newer SCVDs with catalytic activity can provide more cost-effective solutions for industrial and real-life applications.
Keywords: Cavitation; Oxidation; pollution; Technology; Wastewater treatment

Improving hydrodynamic cavitation using newer surface-coated cavitation reactors - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
Surface-coated cavitation devices, vortex diode (SCVD) have been reported for the first time for enhancing efficiency of hydrodynamic cavitation (HC). Two surface-coated cavitation reactors using coating of copper and nickel (-50 mu m) were evaluated, also comparing results with conventional reactor vortex diode. The proof of concept is successfully demonstrated for complete degradation of two model organic pollutants, antibioticscephalexin (CFX) and ciprofloxacin (CIP). The surface-coated reactors provide dual activity, and the catalytic effect is highly pronounced with process intensification using H2O2 and/ or pH alternations. Integration of SCVD, pH and H2O2 was the most effective strategy. Complete degradation of the antibiotics was achieved within minutes with H2O2 (-1000 molar ratio) for both Cu and Ni-surface-coated cavitation reactors compared to lower degradation of-19% for CFX and-37% for CIP using only HC. An excellent enhancement of over 300% for CFX degradation at pH 11 and-170% for CIP degradation at pH 4 was obtained. Huge enhancements in per-pass degradation and cavitational yields (up to 400 times) clearly highlight the utility of the surface-coated cavitation reactors in various applications and for cost-effectiveness.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrodynamic cavitation; Oxidation; pollution; Reactor; Technology; Wastewater treatment